Influences of population size and density on birthplace effects - Hancock, D. J.; Coutinho, P.; Côté, J.; Mesquita, I. (Journal of Sports Sciences, 2018)
Contextual influences on talent development (e.g., birthplace effects) have become a topic of interest for sport scientists. Birthplace effects occur when being born in a certain city size leads to participation or performance advantages, typically for those born in smaller or mid-sized cities. The purpose of this study was to investigate birthplace effects in Portuguese volleyball players by analysing city size, as well as population density - an important but infrequently used variable. Participants included 4062 volleyball players (Mage = 33), 53.2% of whom were men. Using Portuguese national census data from 1981, we compared participants (within each sex) across five population categories. In addition, we used ANOVAs to study expertise and population density. Results indicated that men and women athletes born in districts of 200,000-399,999 were 2.4 times more likely to attain elite volleyball status, while all other districts decreased the odds of expert development. For men, being born in high-density areas resulted in less chance of achieving expertise, whereas there were no differences for women. The results suggest that athletes` infrastructure and social structure play an important role in talent development, and that these structures are influenced by total population and population density, respectively.